Analisis Tegangan dan Kegagalan Yoke Propeller Shaft Truk Angkutan Sawit Menggunakan Metode Elemen Hingga - Tri Satya Ramadhoni; Herlin Sumarna; Toni Okviyanto; Purfaji Purfaji; Rachmat Dwi Sampurno (Yayasan Literasi Sains Indonesia, 2026)
Failure of slip yoke components in palm oil transport vehicle transmission systems is generally caused by complex and cyclic dynamic loading. This study aims to analyze stress distribution and predict failure locations using a Metode Elemen Hingga (FEM)-based approach. A three-dimensional model was developed from actual geometry with controlled simplification using AISI 4140 material. Mesh convergence and quality evaluation were conducted to ensure numerical reliability. The results show that maximum stress increases with load, reaching 196.14 MPa, 294.38 MPa, 392,40 MPa, and 490.52 MPa for loads of 4, 6, 8, and 10 tons, respectively. At 10 tons, the stress exceeds the material yield strength (415 MPa), indicating plastic deformation. Stress concentration occurs at the critical section (C–C) due to geometric discontinuities and combined loading, consistent with observed failure locations. Comparison with analytical results shows less than 1% deviation, confirming model accuracy. This study demonstrates that FEM effectively predicts stress distribution and failure mechanisms, providing a basis for design optimization and maintenance strategies.